Atopic dermatitis with extension tic of the hands. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Case report. An 8-year-old boy had been followed up since birth for a small congenital melanocytic nevus and mild but persistent atopic dermatitis localized predominantly on the flexor surface of the elbows and knees, which recently had involved the hands. Physical examination highlighted asymptomatic erythematous and scaling lesions of the dorsal region of the metacarpophalangeal joint of both hands, with accentuation of the folds and skin furrows. Lesions predominated on the 2nd, 3rd and 4th fingers bilaterally, were less pronounced on the 5th finger and completely absent on the 1st one (Fig. 1). A supplement of history informed us that the child from some time vented his tension extending forcibly his fingers on the metacarpus (inset in Fig. 1). The final diagnosis was extension tic of the fingers in a subject with atopic dermatitis.